2016
DOI: 10.1016/j.mrrev.2016.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ionizing radiation on the heart

Abstract: This article provides an overview of studies addressing effects of ionizing radiation on the heart. Clinical studies have identified early and late manifestations of radiation-induced heart disease, a side effect of radiation therapy to tumors in the chest when all or part of the heart is situated in the radiation field. Studies in preclinical animal models have contributed to our understanding of the mechanisms by which radiation may injure the heart. More recent observations in human subjects suggest that io… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
90
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(92 citation statements)
references
References 146 publications
1
90
0
1
Order By: Relevance
“…Grubber and Dörr consider the radiobiology of the oral mucosa, which is important in light of the adverse reactions to radiotherapy [7]. With respect to effects on the heart and cardiovascular effects, Little reviews the epidemiology [8] and Boerma et al the biology [9]. Hendry and Otsuka provide an overview of intestinal biology [10], and Marjault and Allemand review the effects of radiation on spermatogenesis [11].…”
Section: Introductionmentioning
confidence: 99%
“…Grubber and Dörr consider the radiobiology of the oral mucosa, which is important in light of the adverse reactions to radiotherapy [7]. With respect to effects on the heart and cardiovascular effects, Little reviews the epidemiology [8] and Boerma et al the biology [9]. Hendry and Otsuka provide an overview of intestinal biology [10], and Marjault and Allemand review the effects of radiation on spermatogenesis [11].…”
Section: Introductionmentioning
confidence: 99%
“…Scorpions were collected from the Western Desert in Upper Egypt. The crude venom was collected from scorpion, Leiurus quinquestriatus , with a specific device using electrical shocks at the articular membrane of telson. The collected droplets were aggregated into a clean dry glass container until lyophilization and stored frozen in the dark.…”
Section: Methodsmentioning
confidence: 99%
“…Exposure of the heart to high doses of ionizing radiation has long been known to cause cardiac injury. More recently, clinical, epidemiological, and experimental studies have provided evidence that the cardiovascular system may also be injured by ionizing radiation at low doses …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Previous studies confirmed that high doses of radiation induce both macro and microvascular damage to elevate the risk of cardiovascular disease. 3 Complications of heart disease such as hypertension, atherosclerosis, heart hypertrophy and myocardial infarction might be explained as main causative factors for high mortality rates in the world today. 4 Moreover, ionizing radiation-induced endothelial cell senescence and cardiovascular diseases.…”
Section: Introductionmentioning
confidence: 99%